Effect of Antifungal-Treated Host Macrophages on Candida glabrata. (18th February 2021) - Li, Hong-Bin; Li, Na; Wen, Shu-Ran; Qiang, Ming-Yue; Yang, Zheng-Hui; Dong, Tian-Xiang; Li, Yu-Ye; Kuang, Yi-Qun
Abstract : Objective . Candida glabrata ( C. glabrata ) causes infections associated with severe sepsis and high mortality. This study describes the effects of micafungin (MCF), itraconazole (ICZ), and amphotericin B (AmB) on the function of macrophages during C. glabrata infection. Methods . RAW264.1 macrophages were treated with MCF, ICZ, or AmB and then challenged with C. glabrata . Cytokines from infected macrophage supernatants and the levels of superoxide dismutase (SOD) in macrophages were measured at different time points after phagocytosis. Results . The activity of SOD was significantly increased in RAW264.1 cells that phagocytized C. glabrata and reached a peak level at 6 hours (P < 0.05 ). ICZ and AmB did not affect the SOD activity in cells that phagocytized C. glabrata versus that in untreated macrophage. C. glabrata stimulated macrophages to secrete cytokines. Neither ICZ nor AmB affected the secretion of interleukin-6 (IL-6), interleukin-8 (IL-8), or tumor necrosis factor- α (TNF- α ) by C. glabrata -infected macrophages. However, MCF downregulated the secretion of TNF- α by infected macrophages and reduced the SOD activity of C. glabrata compared with those in untreated controls. Conclusion . Echinocandins may increase their antifungal efficacy by altering the innate immune response of macrophages and attenuating antioxidants of this organism.